2010
DOI: 10.1111/j.1365-2621.2010.02263.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of roasting on the nutritional and antioxidant properties of yellow and white maize varieties

Abstract: Maize varieties (yellow and white) were roasted for 17 min; and allowed to cool, and later milled into powder. The nutritional evaluation (proximate composition, mineral and antinutrient content determination) and antioxidant properties investigation (reducing power, free radicals scavenging ability and Fe 2+ chelating ability) of the product was subsequently carried out. The result of the study revealed that roasting caused a significant increase (P < 0.05) in the crude fat, carbohydrate, Ca, Na, Mg and Zn co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
72
8
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(101 citation statements)
references
References 36 publications
19
72
8
2
Order By: Relevance
“…7.77 − 8.16 and 8.90 − 10.29% respectively. The protein content was comparable with that reported (8.45 − 12.97%) in two maize varieties (Oboh et al, 2010).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…7.77 − 8.16 and 8.90 − 10.29% respectively. The protein content was comparable with that reported (8.45 − 12.97%) in two maize varieties (Oboh et al, 2010).…”
Section: Resultssupporting
confidence: 89%
“…Hwoever, no significant difference was observed in free radical scavenging capacities of ascorbic acids and Trolox. The free radical scavenging activity of these varieties was lower than those reported by Oboh et al (2010) in two different varieties. As IC 50 is the minimum concentration of an antioxidant compounds required to inhibit the 50% of free radical, a lower IC 50 value indicates a higher antioxidant activity.…”
Section: Resultscontrasting
confidence: 74%
See 2 more Smart Citations
“…Arora et al 2009 also revealed increased in vitro minerals availability after autoclaving of fermented food mixtures. Reduction in antinutrients after heat treatment is in consonance with the findings of Vadivel and pugalenthi (2008) and Oboh et al (2010) who attributed it to the high temperatures. Lakra and Sehgal (2011) also found higher mineral availability and lower antinutrient after frying and fermentation of potato flour.…”
Section: Resultssupporting
confidence: 89%